Chapterhouse Dune [compact disc, unabridged] - Herbert, Frank (Herbert, Frank. Dune chronicles, 2009)
The desert planet Arrakis, called Dune, has been destroyed. Now, the Bene Gesserit, heirs to Dune's power, have colonized a green world--and are turning it into a desert, mile by scorched mile.